Rubrik Nursing Clinical Exercise: Pengembangan Instrumen Penilaian Kompetensi Klinis Pada Pendidikan Klinik Keperawatan - Retno Sumiyarrini; Gandes Retno Rahayu; Yoyo Suhoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Clinical Skills is a fundamental ability that must be mastered by the newly graduated nurses. Therefore, assessment of clinical competence is essential to be considered by educators and education managers. It needs a valid assessment instrument, which is reliable and impactful on learning the process by giving a structured feedback so that qualified graduates can be produced. Some assessment instruments in the clinical nursing education have less evidence of validity and reliability and less feasible, so it requires a development of clinical assessment instruments. This study aims to develop a clinical assessment instrument in the nursing clinic and to test the content validity. Method: This study used a qualitative research design that includes drafting through literature review and expert review by the expert panel.Results: The process of drafting and reviewing produces a rubric named Nursing Clinical Exercise (NCEx) made of six domains consisting the assessment of subjective data, physical examination, diagnosis formulation, treatment planning formulation, communication and interpersonal relationships, and professionalism. The value of content validity is good (CVR of the entire domain = 1)Conclusion: The NCEx Rubric consists of six domains and has good content validity.